2021
DOI: 10.3390/cancers13215398
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of an Efficient MRI Radiomics Signature for Improving the Predictive Performance of 1p/19q Co-Deletion in Lower-Grade Gliomas

Abstract: The prognosis and treatment plans for patients diagnosed with low-grade gliomas (LGGs) may significantly be improved if there is evidence of chromosome 1p/19q co-deletion mutation. Many studies proved that the codeletion status of 1p/19q enhances the sensitivity of the tumor to different types of therapeutics. However, the current clinical gold standard of detecting this chromosomal mutation remains invasive and poses implicit risks to patients. Radiomics features derived from medical images have been used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 53 publications
(106 reference statements)
0
10
0
1
Order By: Relevance
“…For instance, Le et al [ 25 ] used the Spearman correlation test and F-score analysis to find significant features for glioblastoma identification. Kha et al [ 26 ] employed SHAP analysis, a machine learning model, to find a radiomics signature for 1p/19q codeletion status prediction. A novel method for feature selection was conducted in our study where an incorporated model of the genetic algorithm (GA) and machine learning algorithms was developed to identify the radiomics signature.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Le et al [ 25 ] used the Spearman correlation test and F-score analysis to find significant features for glioblastoma identification. Kha et al [ 26 ] employed SHAP analysis, a machine learning model, to find a radiomics signature for 1p/19q codeletion status prediction. A novel method for feature selection was conducted in our study where an incorporated model of the genetic algorithm (GA) and machine learning algorithms was developed to identify the radiomics signature.…”
Section: Discussionmentioning
confidence: 99%
“…A challenge XAI helps address is identifying only the most important features predictive of the outcome, which improves final model feature selection, thus eliminating the irrelevant ones, leading to a better model that is more robust and less prone to overfitting. Kha et al have reported on identification of a radiomic signature predictive of 1p/19q co-deletion ( 34 ). During model development, the SHAP framework was used to identify the most important features to include in their model, leading to improved model performance when less important features, based on average SHAP values, were removed, with an AUC of 0.710 before feature selection and 0.753 after.…”
Section: Utilization Of Xai In Oncology Researchmentioning
confidence: 99%
“…1p/19q co-deletion refers to the combined deletion of the short arm of chromosome 1 and the long arm of chromosome 19, which can occur in various glioma subtypes, with oligodendroglioma being the most common, and GBM having a very low incidence. Many studies have demonstrated that 1p/19q co-deletion status enhances tumor sensitivity to different types of treatments [61]. Therefore, gliomas with 1p/19q co-deletion are sensitive to chemotherapy and have a significantly improved prognosis.…”
Section: P/19q Co-deletionmentioning
confidence: 99%